Evaluate the Capabilities and Limitations Sustainable Rural Development in the Kermanshah District - AliAkbari, Masood Safari; Pishroo, Hamdollah (International Journal of Geography and Geology, 2014)
The purpose of this paper is to investigate the capabilities and limitations sustainable rural development in the Kermanshah district, is. Kermanshah district is, the one of Kermanshah city in the Kermanshah Province, located in the West of Iran. Province with an area of 24,640 square kilometers, the seventeenth province of Iran, the extent of. Reviews features and capabilities of the rural Kermanshah district, in order to achieve sustainable development goals of the study is considered. To assess the capabilities and limitations of sustainable rural development, Kermanshah district, the Model " driving force ( pressure), - the status quo - Response " (PSR), with emphasis on economic factors, is employed. In order to sustain economic factors are the factors that leads to rural development in a period of sustained economic terms, and the amount of economic and social prosperity for farmers and villagers to create. In the model used, studied over 10 indicators, such as access to water resources, food security, adequate income and permanent farmer’s share of manufactured exports, etc. have been studied. To calculate the index, data from the Statistical Center of Iran and the Ministry of Agriculture has been used. The results of the model used, the indicators used, show that stability, rural development, agricultural activities down to reliance has been, and continues to the present situation cannot be sustainable development for rural areas surveyed have. One of the main reasons for this instability, the increasing cost of agricultural production, on the one hand, and the low prices of the other party, which has caused the value added of this sector was low and income from agricultural activities 30 percent of total rural income ), not sustainable rural development, to be held.